An investigation into the walkability problem in Indian cities. Issue 2 (10th April 2017) - Bharucha, Jehangir
Abstract : Purpose: Indian cities have always been cities of walkers. The purpose of this paper is to attempt to examine the walkability of Mumbai city and outlines the problems, challenges and scope for improving its walkability. Design/methodology/approach: Five typical districts of Mumbai city were chosen for the field study. Within each of these districts, certain walking routes were mapped. A survey of 100 people belonging to the middle class and lower middle class was conducted via a structured questionnaire pertaining to the pedestrian difficulties and solutions. The researcher along with a group of students then actually walked each of the routes and collected more specific information. Findings: It is observed that Indian cities are becoming increasingly unsafe for pedestrians. Sidewalks and pavements just do not exist. If a pavement exists it is poorly constructed and badly maintained. An attempt was made to derive a walkability rating for the city of Mumbai. Practical implications: This study highlights several policy recommendations for enhancing the current pedestrian infrastructure and gives pedestrian-focused solutions. Originality/value: Very little work has been done by the way of theory and methodology to plan and mould walkable cities. A change in focus is needed that puts people at centre stage.